Youth Political Participation in Italy: The Case of the Student Movement for Palestine - Andretta, Massimiliano; Imperatore, Paola (PARTECIPAZIONE E CONFLITTO, 2025)
In a context of deep crisis of democratic institutions - one that has increasingly alienated younger generations from both conventional and unconventional forms of participation - the wave of pro-Palestinian mobilization that has swept across the globe over the past year appears to have reversed a long-standing trend. In Italy, as elsewhere, a new generation of young people has taken the lead in global mobilization for the liberation of Palestine, often identifying the university as both a privileged site and a symbolic target of contestation. This article seeks to reconstruct the key features of this phase of student mobilization and politicization, to highlight the local and global factors that have shaped its development, and to explore the meanings and practices that define it.